Future directions in distance learning and communications technologies - Shih, Timothy K. 1961-; Hung, Jason C. 1973- (Gale virtual reference library, 2007)
This book summarizes theoretical studies and practical solutions for engineers, educational professionals, and graduate students in the research areas of e-learning, distance education, and instructional designs. Readers will find solutions and research directions in this interesting book.